CSR – An Important tool for Employer Branding. - Tope, Bhupendra Chandrashekhar; Khatke, Dr. Mrs. Anita (The journal of contemporary issues in business and government, 2021)
An employer branding can be understood as a set of procedures which instigates with the contact for the very beginning of the probable candidate with the organisation brand. This stream flows endlessly through every phase of the association journey. This journey may be referred as the “Talent Journey”. It includes the details, additional information, and complete data required behind the recruitment and selection process, keeping the candidate pleased, engaged, and loyal to the organisation. It also provides insights into how keenly and enthusiastically employees of the organisation endorse working at the specific organisation. “An employer brand is an intangible. However, many tangible practices and behaviors contribute to it.” Edward E. Lawler. Employees engaged in CSR activities perform to their best and create a special place for the organisation in the market. An organisation is considered successful where the employees of that particular organisation feel valued because of their loyalty. This feeling of loyalty comes with the exponential organisational support and the management standing by with their commitments. Providing such kind of support and fulfillment of commitments towards the employees gives that organisation a better identification in the industry because employees don’t wish to leave such organisations. Employees working with such organisations always consider themselves accountable for the success in building the brand image. In these types of organisations, the attrition goes down, best talent stays back and hence the face value of the company automatically goes up. The main objective of this research article is to understand importance of CSR in Employer Branding and elements of CSR in Employer Branding. "Employer Branding," an essential aspect of the business, is considered a crucial element in every organisation's success. A factor that takes the business entity to a different level and proves to be one of the best practices in promoting the brand image. In recent times, aspiring candidates have become very vigilant in joining any particular organisation. They first check all the credentials of an organisation and then decide whether to join it or not. Hence, from the employee's perspective, Employer Branding has gained an important place in promoting an organisation as an 'Employer of Choice.' A positive image portrayed by gaining employee confidence helps in gaining much popularity in the market. Since this is article has been written by referring to various journals, research articles and a book, Conceptual Research Methodology has been used to understand the topic in depth.